Camden Avenue demonstration - Sahl, Ted (photographer):::Creator::::::::::::
Ed Sebesta, President of Lesbian & Gay Associated Engineers and Scientists (LGAES) (left) and a pastor from the Los Gatos Christian Church on Camden Avenue. A sign is partially obscured from full view, and reads: April 6, 1925, John Thomas Scopes...evolution."